Pediatricians' perspectives on pneumococcal conjugate vaccines: An exploratory study in the private sector - Sanjay Zodpey; Habib Hasan Farooqui; Maulik Chokshi; Balu Ravi Kumar; Naveen Thacker (Wolters Kluwer Medknow Publications, 2015)
There is a lack of information on supply-side determinants, their utilization, and the access to pneumococcal vaccination in India. The objective of this exploratory study was to document the perceptions and perspectives of practicing pediatricians with regard to pneumococcal conjugate vaccines (PCVs) in selected metropolitan areas of India. A qualitative study was conducted to generate evidence on the perspective of pediatricians practicing in the private sector regarding pneumococcal vaccination. The pediatricians were identified from 11 metropolitan areas on the basis of PCV vaccine sales in India through multilevel stratified sampling method. Relevant information was collected through in-depth personal interviews. Finally, qualitative data analysis was carried out through standard techniques such as the identification of key domains, words, phrases, and concepts from the respondents. We observed that the majority (67.7%) of the pediatricians recommended pneumococcal vaccination to their clients, whereas 32.2% recommended it to only those who could afford it. More than half (62.9%) of the pediatricians had no preference for any brand and recommended both a 10-valent pneumococcal conjugate vaccine (PCV10) and a 13-valent PCV (PCV13), whereas 8.0% recommended none. An overwhelming majority (97.3%) of the pediatricians reported that the main reason for a patient not following the pediatrician's advice for pneumococcal vaccination was the price of PCV. To reduce childhood pneumonia-related burden and mortality, pediatricians should use every opportunity to increase awareness about vaccine-preventable diseases, especially vaccine-preventable childhood pneumonia among their patients.